The original copy shop: eclipses and exemplars. Issue 3 (3rd July 2019) - Reeves, Eileen
Abstract: This article examines the notion of the copy as it developed in early modernity, focusing in particular on its persistent association with the projection of sunlight through apertures, and with the special case of the solar eclipse, where the sun is partially or fully occluded by the lunar globe. It argues for the importance of these two optical models as allegories of the constant and imperfect transmission of images and, more surprisingly, of texts. Both models privilege an effaced original, a substantive absence emerging only as a retrospective effect of the copy. At issue, then, are the ways in which poets and natural philosophers, and the confederates they found in translators, commentators, printers, and philologists, portrayed the transmission of word and image, particularly with the advent of print. This configuration of the effaced original and the ambitious successor applies to Johannes Kepler's relationship with the imperfectly known work of Francesco Maurolico, and to Horace's association with the fragmentary œuvre of his legendary Greek predecessor Archilochus. As argued, scrutiny of the optical problem of the transmission of light produced not simply a model for replicated images, but, more crucially, one for the reception and reproduction of texts.